“Look who is laughing now” - Deborah Jump (Oñati Socio-Legal Series)
This paper’s aim is to further current thinking around young men’s perceptions and understanding of violence, and the use of boxing as a vehicle in the prevention of repeat victimization. The focus is on the use of bodily or physical capital, and the ways in which men draw upon this resource to ward off attacks to identity and psyches, especially those perceived as disrespectful. It will draw on data from The Criminology of Boxing, Violence and Desistance (Jump 2020), and present overarching ideas from Tyrone, a psychosocial case study highlighting the underpinning theory and its development. This paper disrupts common discourses that argue that boxing is a panacea for all violence, and thus presents more subjective nuanced accounts of men’s lives in the gym, and the streets. In using the term “physical capital”, I employ Wacquant’s (1995) theory, and suggest that boxers not only use their body as a “form of capital” (p. 65), but that the physical capital accrued through the corporeal praxis of boxing, is actually a way to disavow prior victimization, and invest in the prevention of repeated traumatic scenarios.